Innovative approach for the determination of unit weight and density of soil and rock masses - Discenza, Marco Emanuele; De Pari, Pierfederico; Kundu, Jagadish; Minnillo, Mariacarmela; Romano, Sergio; Scarascia Mugnozza, Gabriele (Italian journal of engineering geology and environment, 2021)
<span data-sheets-value=""1":2,"2":"The present paper aims to develop an analytical approach for defining the two most important physical properties of soils and rocks at mass scale: unit weight and density. A series of equations have been developed for the calculation of the aforementioned parameters for different types of soil and rock masses available in nature; specifically homogenous, jointed, layered, and chaotic masses. The relationships were determined according to an “equivalent continuum approach” by analyzing the physical characteristics and volumetric fractions of different elements that make up the mass, such as discontinuities, layers, and blocks. The required inputs for the proposed equations are limited in number and easily obtainable by conventional site surveys and laboratory tests. Each of the equations has been validated through the application to several case studies representative of soil and rock masses with different physical conditions. The proposed relationships show a high degree of reliability and are therefore applicable to different types of soil and rock masses, according to the developed standardized and repeatable approach."" data-sheets-userformat=""2":13057,"3":"1":0,"11":3,"12":0,"15":"Arial","16":8">The present paper aims to develop an analytical approach for defining the two most important physical properties of soils and rocks at mass scale: unit weight and density. A series of equations have been developed for the calculation of the aforementioned parameters for different types of soil and rock masses available in nature; specifically homogenous, jointed, layered, and chaotic masses. The relationships were determined according to an “equivalent continuum approach” by analyzing the physical characteristics and volumetric fractions of different elements that make up the mass, such as discontinuities, layers, and blocks. The required inputs for the proposed equations are limited in number and easily obtainable by conventional site surveys and laboratory tests. Each of the equations has been validated through the application to several case studies representative of soil and rock masses with different physical conditions. The proposed relationships show a high degree of reliability and are therefore applicable to different types of soil and rock masses, according to the developed standardized and repeatable approach.